(untitled) (Research, Society and Development, 2022)
The process of cooling and freezing fish in slaughterhouses, transport, and storage until it reaches the final consumer has high costs in the production chain. Some fish species have low commercial value, especially those that at the time of harvest are undersized for industrial processing. To analyze a possible alternative to add value to fish, this work evaluated the quality presented by canned four freshwater fish species: Tilapia (Oreochromis niloticus); Tucunaré (Cichlao cellaris); Piavuçu (Leporinus macrocephalus), and Lambari (Astyanax altiparanae), both prepared in brine and in pâté. Twenty-four 270 grams cans of these canned fish were used and bromatological, microbiological and sensory analyses were performed. The sensory analysis was performed by 35 testers, who assigned scores from 1 to 9 for organoleptic attributes, such as appearance, aroma, flavor, color, consistency, and overall impression. The data were submitted to several statistical analyses, such as: Analysis of Variance (ANOVA), Principal Component Analysis (PCoA), Permutational Analysis of Variance (PERMANOVA). The results indicate a higher preference for fish in pâté form and a good acceptance of the piavuçu, tilapia and tucunaré canned brine. The analyses of purchase intention of the canned fish followed the sensorial test, showing better purchase intentions for the canned fish in pâté form, and a good purchase intention for the canned Lambari, Piavuçu and Tilapia. Therefore, the use of canned fish in brine and pâté may constitute a viable alternative to add value to the fish, well as enable the diversification of products derived from this raw material, easy to prepare, without the need for refrigeration.